PERBANDINGAN PENDAPATAN PENJUAL BUAH PADA SAAT LIBUR DAN BUKAN LIBUR DI DESA TALAWAAN - Thirza ., Kambey; Paulus A. Pangemanan; Mex L. Sondakh (Sam Ratulangi University, 2017)
The objective of this research is to know rambutan fruit income ratio during holiday and not holiday. This research was conducted in Talawaan Village Talawaan Subdistrict. For three months, ie from June to August 2015, from preparation, data collection to the preparation of research reports. The data used are primary data obtained through interviews to 20 (twenty) respondents of rice farmers and 20 respondents for sellers of Rambutan Fruit and secondary data obtained from the government of Talawaan subdistrict of North Minahasa. Data analysis used in this research is descriptive analysis, where the data collected will be presented in tabular form. The results showed that agro-tourism influenced the income of rambutan fruit seller is seen from the day of the holiday increment compared to the day is not a holiday.